EFISIENSI BANK DAN RETURN SAHAM PADA SEKTOR PERBANKAN SELAMA PERIODE TAHUN 2013-2021 - Hamzah, Salman; Deliyana , Sita (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to comprehend the interaction between bank efficiency and its stock performance in Indonesia. The sample for this research consists of 31 banking companies listed on the Indonesia Stock Exchange (IDX) from the period of 2013 to 2021. To assess the level of bank efficiency, a non-parametric method, Data Envelopment Analysis (DEA) will be employed. Meanwhile, a panel data regression analysis will be utilized to investigate the influence of bank efficiency on the performance of Indonesian banks' stocks. The results of the DEA analysis indicate fluctuations in the level of bank efficiency from year to year, which could possibly be attributed to global economic conditions. Conversely, the regression analysis results show that the level of bank efficiency does not exhibit a significant relationship with stock returns. This suggests that efficiently operated banks do not always yield better stock performance in the stock market.